Asymptotic uniform moduli and Kottman constant of Orlicz sequence spaces - Delpech, Sylvain (Revista Matemática Complutense, 2009)
We give lower and upper bounds, involving moduli of asymptotic uniform convexity and smoothness, for the Kottman separation constant of Orlicz sequence spaces equipped with the Luxemburg norm.
Keywords: Modulus of asymptotic uniform convexity; Modulus of asymptotic uniform smoothness; Kottman constant; Orlicz sequence space